Development and test of a simplified method to calculate dry matter loss during open-air storage of poplar wood chips by analysing ash contents. (November 2016) - Lenz, Hannes; Pecenka, Ralf; Hartung, Eberhard; Idler, Christine
Abstract: Short rotation coppice (SRC) in agriculture can be established successfully, only if the entire process chain is economically competitive. Despite the substantial dry matter loss (up to 25%) occurring during open-air storage of wood chips, it is the most applied storage technique. Since the particle size of wood chips plays an important role in storage and drying processes, two storage piles (>500 m 3 ) with fine and coarse wood chips were investigated comprehensively under the weather conditions of North-East-Germany over a period of 9 months. The objective of this experiment was to develop a simplified method to calculate dry matter loss by determining the ash content and to compare the results with the conventional sample bag method. The new method delivered statistically sound results, particularly when ash contents were calculated from separated bark and wood samples instead of from wood chip samples. Furthermore, the significant and consistent increase in ash content of the bark samples during storage suggests, that the development of a model solely based on ash content of separated bark could be advantageous in terms of simplified yet reliable determination of dry matter losses. Since the ash content of wood chips is largely governed by the bark content, exact data for the proportion of bark is required, which varies between 18 and 35% depending on tree size represented by the stem diameter at cutting height (SDCH). Moreover, it was found that the fuel quality depends more on the SDCH of the SRC-harvest than on the produced wood chip format. Highlights: Storage characteristics for fine and coarse wood chips from poplar were investigated over a period of 9 months. The investigations were carried out in typical practice size storage piles (>500 m 3 per pile). The correlation between mass losses and ash contents were analysed in detail. The ash content of wood chips is mainly determined by the stem base diameter of the trees at harvest. A simplified method has been developed to calculate dry matter losses by means of ash content changes during storage.